2004
DOI: 10.1080/02643290342000258
|View full text |Cite
|
Sign up to set email alerts
|

Brain potentials reflect residual face processing in a case of prosopagnosia

Abstract: Here, ERPs were employed to characterise the residual face processing of FE, a patient with extensive damage to the ventral temporal-occipital cortex and a dense prosopagnosia. A large N170 was present in FE and he performed well in tests of face structural processing. Covert recognition of the faces of personal acquaintances was demonstrated with P300 oddball experiments. The onset latency of the P300 effect was normal, indicating fast availability of covert memory. The scalp topography of this component in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 88 publications
(136 reference statements)
1
25
0
Order By: Relevance
“…Although a relative absence of an increased N170 amplitude for faces as compared with objects may relate to face recognition problems (28)(29)(30), other cases of prosopagnosia have not shown this pattern (31,32). One explanation of this diverse pattern again observed here may be that the N170 is, in addition to the encoding of the whole face, related to the perception of facial features and may reflect the extent to which a featural strategy is adopted.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although a relative absence of an increased N170 amplitude for faces as compared with objects may relate to face recognition problems (28)(29)(30), other cases of prosopagnosia have not shown this pattern (31,32). One explanation of this diverse pattern again observed here may be that the N170 is, in addition to the encoding of the whole face, related to the perception of facial features and may reflect the extent to which a featural strategy is adopted.…”
Section: Discussionmentioning
confidence: 61%
“…For some prosopagnosic cases, the N170 did not show the characteristic increased amplitude for faces as compared with objects (28-31), whereas for other cases an increase of the N170 for faces relative to objects was reported much as in normal subjects (31,32). This lack of consistency may be related to the heterogeneous nature of developmental disorders like prosopagnosia and is in line with mixed results obtained in behavioral (9,20,33) and functional MRI studies (34)(35)(36), mostly of single patients.…”
mentioning
confidence: 53%
“…This patient suffered extensive bilateral damage to his ventral occipito-temporal cortex (Lopera and Ardila, 1992), which produced a severe deficit in face identification. He also exhibited robust emotionally-based covert recognition of the same previously-known faces that he was unable to recognize consciously (Bobes et al, 2004). The study of FE suggested that a previously ignored pathway (and not the fusiform-temporal route) was responsible for his covert face processing.…”
Section: Introductionmentioning
confidence: 93%
“…Another expression of covert recognition is an increased emotional arousal to NeuroImage 57 (2011NeuroImage 57 ( ) 1162NeuroImage 57 ( -1176 faces of celebrities or acquaintances relative to unfamiliar faces, as indexed by larger skin conductance responses -SCRs - (Bauer, 1984;Bobes et al, 2004;Tranel and Damasio, 1985) and P300 brain waves (Bobes et al, 2004;Renault et al, 1989). Also, implicit preference for some faces, which indicates access to memories for their emotional valence, has been found in AP (Bobes et al, 2004;Tranel and Damasio, 1993). Note that activation of emotional memories by known faces is conceptually distinct from the processing of facial expressions.…”
Section: Introductionmentioning
confidence: 99%
“…2 Especially the latter has been found to be sensitive to the recognition of familiar faces, whether famous (Henson et al, 2003), learned during a study phase (Joyce and Kutas, 2005;Paller et al, 1999Paller et al, , 2000Paller et al, , 2003, or the participant's own face (Ninomiya et al, 1998). Moreover, a late positive ERP component in response to familiar faces has even been observed in prosopagnosia patients, regardless of their incapability of familiar face recognition (Bobes et al, 2004;Renault et al, 1989). However, paradigms used in the studies cited above vary greatly and in each case deviate from a typical P300 based CIT.…”
Section: Introductionmentioning
confidence: 95%